(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This paper examines how green fiscal instruments support renewable energy development and contribute to economic growth and environmental sustainability. The analysis focuses on feed-in tariffs, renewable energy subsidies, and tax incentives as key policy tools used to encourage investment in clean energy technologies. A review of recent empirical studies shows that these instruments can accelerate renewable energy deployment, reduce greenhouse gas emissions, and stimulate innovation and employment. At the same time, their effectiveness depends on policy design, institutional quality, and the broader economic context. The study concludes that well-targeted fiscal measures are important for achieving a balanced transition toward low-carbon and sustainable economic development.